Prevalence and pattern of tobacco use among auto rickshaw drivers of South Delhi: a cross-sectional study - Arora, Priya; Kaur, Gurmeet; Khokar, Anita; Jindal, A. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Tobacco is one of the major preventable causes of death and disability worldwide. Tobacco related diseases are a burgeoning public health problem. The pattern of tobacco consumption in India is unique as varied smoked and smokeless products are consumed. Methods: Descriptive, cross-sectional study. Results: 69% of the auto-rickshaw drivers are currently using tobacco in one form or the other. Use of multiple tobacco products is also quite high; 54% of tobacco users consumed both smoked as well as smokeless forms of tobacco. Bidi smoking is the most common form of tobacco consumption among current users. Conclusions: Tobacco consumption among auto rickshaw drivers is high. The use of multiple products puts them at risk for problems related to both smoked and smokeless tobacco products. Support/services to quit tobacco should be targeted at their workplace as stress and free time during working hours have been cited as main reasons for tobacco consumption.